Un corpus de sculptures sur pierre du haut Moyen Âge (Ve-Xe s.) en Gaule du Nord - Laure-Anne Finoulst (Les Cahiers de l'École du Louvre)
The early medieval sculptures of northern Gaul do not yet benefit from a real corpus. Information about them is often sparse and incomplete. They are usually discovered near reused materials, posing problems of dating and determination of function, given their fragmentary state. This is an extended update of an inventory published in 2019, which currently includes 223 items, for which the place of discovery, presumed function and decorations are briefly described. This overview allows us to make initial hypotheses about their nature, uses and main motifs, as well as about their location in the geographical area concerned. The inventory and study are to be continued.